Gruppenaufnahme - Thomas Köhler
Ministerpräsident Baden-Württemberg Erwin Teufel; CDU-Generalsekretär Laurenz Meyer; Vorsitzender CDU/CSU-Bundestagsfraktion Friedrich Merz; CDU-Vorsitzende Angela Merkel;